2021
DOI: 10.3390/en14217096
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the UK Continental Shelf Electrification Potential for Offshore Oil and Gas Installations: A Power Grid Architecture Perspective

Abstract: Most of the UK Continental Shelf (UKCS) oil and gas (OG) installations have traditionally adopted in situ power generation, which is not only inefficient but also generating about 70% of the offshore CO2 emissions. The offshore wind and energy storage technologies for deep water are developing at a fast pace, enabling great opportunities for the OG installations located in the North Sea. In this paper, a pathway for the UKCS offshore OG installations electrification is introduced. The aim is to provide differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Based on the optimal solutions under different conditions showed in Figs. 13,16,18 and 21, we notice that offshore wind is a relatively cost efficient technology that can achieve moderate emission targets of platforms. This may suggest that in countries where PFS is not an option, offshore wind alone can still help emission reduction to a large extent.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on the optimal solutions under different conditions showed in Figs. 13,16,18 and 21, we notice that offshore wind is a relatively cost efficient technology that can achieve moderate emission targets of platforms. This may suggest that in countries where PFS is not an option, offshore wind alone can still help emission reduction to a large extent.…”
Section: Discussionmentioning
confidence: 90%
“…The potential value and functioning of OEHs have drawn increased attention in several sectors. In the offshore oil and gas sector, it has been found that creating small energy hubs to import energy from various sources to offshore oil and gas platforms can achieve a massive reduction of CO 2 emissions in the UK continental shelf [18]. They mentioned that hydrogen-energy storage is green and provides supply security for oil and gas operations.…”
Section: Oehsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the expansion of the scale of offshore oil and gas field exploitation, in order to improve the reliability of power supply in the production process, the power supply mode of the offshore oil group gradually transits from the traditional power supply of each platform power station to the combined power supply between the platform power stations. The platforms are connected by submarine cables to form the offshore oil group power grid [1][2]. Although the scale of the offshore oil group power grid is smaller than that of the land power grid, it contains the necessary links of the land power grid such as generation-transport-transform-distribution, and is a specific offshore oil group power grid.…”
Section: Introductionmentioning
confidence: 99%
“…However, few of these studies propose a grid connection as backup to supply the assets when no wind is blowing and receive the surplus wind energy at low power demand. In general, electrification concepts for offshore assets could be divided into three categories depending on their distance from shore: powering assets via direct grid connection (HVAC or HVDC transmission lines) where no wind energy is included [4]; powering assets from grid-connected offshore wind farms [4]- [6] and lastly, powering assets via islanded micro-grids when they are further from shore [5], [7]- [14].…”
Section: Introductionmentioning
confidence: 99%